Introductory mycology - Alexopoulos, Constantine John, 1907-1986 (John Wiley & Sons, 1996)
Revised edition (the third [1979] is cited in BCL3) of a phylogenetically-based textbook that comprehensively covers all the organisms traditionally considered as fungi, rather than only the four phyla comprising the kingdom Fungi. The first three chapters, as well as those chapters and chapter sections that introduce the various phyla, are appropriate for shorter undergraduate and graduate courses, while other sections relating to specific groups of fungi are considerably more detailed. Thoroughly illustrated and extensively referenced.